(untitled) (Revista Sistemas de Producción Agroecológicos, 2010)
This work was conducted at the Universidad de los Llanos located on the Barcelona hamlet, Meta Department, Colombia. In this investigation was evaluated the nutritional quality of silages prepared with forage trees: Cratylia argentea, Hibiscus rosa-sinensis, Trychanthera gigantea and Tithonia diversifolia. The species were sown in plots, and then made a pruning and were harvested 60 days after which leaves were kept silages 5 kg, leaving four periods of maturation (0, 30, 60, 90 days). The silage was analyzed in the Laboratory of Animal Nutrition: dry matter (DM), ash, fat, protein, crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), nitrogen joined FDN (NFDN), cellulose, and lignin. Cratylia, argentea (32.6%) was produced more dry matter than Tithonia diversifolia (30%), Hibiscus rosa-sinensis (28.5%) and Trychanthera gigantea (25%). Although there was an increase of DM with increasing the retention period of silage (0, 30, 60 and 90) as increases FDN, FDA and lignin in these four forage species too. The protein in the four species decreased with longer maturity of these forage silage, this reduction was greater in Cratylia argentea (8.2%) compared with others: Hibiscus rosa-sinensis (6%), Trychanthera gigantea (6%) and Tithonia diversifolia (4%).